Rancang Bangun Sistem Pendingin Adsorpsi Dengan Pasangan Karbon Aktif-Metanol Sebagai Adsorben -Adsorbat - Martin, Awaludin; Hariyono, Hariyono (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The air conditioning system is used during nowdays is vapor compression system that uses high energy and refrigerant that can damage the ozone layer and global warming increasing. Adsorption cooling system with activated carbon as adsorbent and methanol as adsorbate is expected to replace the vapor compression system that utilizes a high energy, using refrigerants that could potentially damage the ozone layer and the increase of global warming. This study aims to determine the value of COP adsorption cooling system was designed and fabricated. The method used in this research is the design. Method engineering is done for the design, manufacture, and testing of adsorption refrigeration using activated carbon-methanol pair as adsorbent-adsorbate. Based on test data obtained, the lowest temperature of the water coming out of the evaporator is 21.8 Â°C with the highest temperature change was 2.9 Â°C and the average water temperature change is 2.31 oC. COP values of adsorption cooling system was designed and fabricated at 0.0439.Keywords : Adsorption, COP, Actiated Carbon, Methanol